SISTEM PENAGIHAN PIUTANG ATAS PENGANGKUTAN IMPOR LAUT: OLEH PT. BANGUN PUTRA PESAKA - Novita Pakpahan; Fharel M .Hutajulu; Desideria Regina (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
There are many companies in Indonesia conducting import, usually these companies in conducting import goods using the services of Customs Clearance Services Companies (PPJK) and Sea Cargo Ship (EMKL). The payment for services that have been performed by PPJK and EMKL in terms of loading and unloading of import and transport to the importing company warehouse is usually done with the receivables. Services are rendered and then calculated the amount of the value of services performed and finally sends the bill to the importer company for services performed.Keywords : billing and deliver